Illicit Drugs, Organised Crime, and Violent Extremism: Addressing the Nexus, Countermeasures, and Implications - Ebonyi, Anthony A.; Bello, Bashir (ABUAD Journal of Social and Management Sciences, 2024)
This article explores how illicit drug traffickers, organised criminals, and violent extremists interact along intricate pathways to perpetrate their illegal activities and recommends how security agents, especially the National Drug Law Enforcement Agency (NDLEA) can better tackle the activities of illicit drug racketeers linked to organised criminal groups and violent extremists. Against this backdrop, the article provides an analysis of the association between illicit drugs, organised crime, and violent extremism. The study was an exploratory research design, carried out in Tsafe Area of Zamfara State. It was conducted using a Key Informant and In-depth Interview. The research was conducted using the snowballing sampling method. Findings revealed that while efforts to curtail the phenomenon are ongoing, the linkages are getting stronger daily. Therefore, to combat the increasing activities of these organised criminal groups, the article recommends a multi-sectoral and “whole systems” approach using modern technology, and synergy among agencies of government, as well as non-governmental stakeholders, who have the wherewithal to support actions being undertaken by the government.